Dose reduction of biologics in patients with plaque psoriasis: a review - van Riel, C. A. M.; Michielsens, C. A. J.; van Muijen, M. E.; van der Schoot, L. S.; van den Reek, J. M. P. A.; de Jong, E. M. G. J. (Frontiers in Pharmacology, 2024)
Dose reduction (DR) of the first generation biologics for plaque psoriasis (TNF-alpha inhibitors (i) and interleukin (IL)-12/23i) have been described in a previous scoping review.Literature on DR of the newest generation biologics (IL-17/23i) was scarce. The current review provides a literature update of the previous scoping review on DR of all biologics including the newest generation, with as new aspect uptake and implementation of DR in practice. The current literature search on DR revealed 14 new articles additional to those in the previous review. Four newly found articles tested DR strategies, regarding mostly first generation biologics; only guselkumab (IL-23i) was included in one study. The other ten studies showed data on regaining response after failure of DR, safety, cost-effectiveness and on uptake and implementation, with also information on IL-17/23i. Eligibility criteria to start DR included both absolute and relative PASI scores (PASI≤3/≤5/PASI 75-100), and/or DLQI≤3/≤5, or BSA ≤1/≤2, or PGA≤1/0-2 during a period ranging from 12 weeks to ≥1 year.Most studies used PASI≤5, and/or DLQI≤5, or PGA≤1 for ≥6 months. DR strategies were mostly performed by stepwise interval prolongation in two steps (to 67% of the standard dose, followed by 50%). Some studies of IL-17/23i reduced the dose to ±25%. Tested DR strategies on stepwise or fixed DR on TNF-αi and IL-12/23i (3 studies), as well as one 'on demand' dosing study on IL-23i guselkumab, were successful. In case of relapse of DR on TNF-α-i and IL-12/23i, clinical effectiveness was regained by retreatment with standard dose.All studies showed substantial cost savings with biologic DR of TNF-αi and IL-12/23i. Identified barriers against implementation of DR were mainly lack of guidelines and scientific evidence on effectiveness and safety, and lack of time and (technical) support. Identified facilitators were mainly clear guidelines, feasible protocols, adequate education of patients and physicians, and cost reduction. In conclusion, DR seems promising, but there is still a research gap in randomized, prospective studies testing DR strategies, especially of IL-17/23i hampering the completion of guidelines on DR. Taking into account the identified barriers and facilitators results most likely in a more successful implementation of biologic DR in practice.